Membrane physical state controls the signaling mechanism of the heat shock response in Synechocystis PCC 6803: Identification of hsp17 as a “fluidity gene” - Horváth, Ibolya (The National Academy of Sciences, 1998)
The fluidity of Synechocystis membranes was adjusted in vivo by temperature acclimation, addition of fluidizer agent benzyl alcohol, or catalytic lipid hydrogenation specific to plasma membranes. The reduced membrane physical order in thylakoids obtained by either downshifting growth temperature or administration of benzyl alcohol was paralleled with enhanced thermosensitivity of the photosynthetic membrane. Simultaneously, the stress-sensing system leading to the cellular heat shock (HS) response also has been altered. There was a close correlation between thylakoid fluidity levels, monitored by steady-state 1,6-diphenyl-1,3,5-hexatriene anisotropy, and threshold temperatures required for maximal activation of all of the HS-inducible genes investigated, including dnaK, groESL, cpn60, and hsp17. The causal relationship between the pre-existing thylakoid physical order and temperature set point of both the transcriptional activation and the de novo protein synthesis was the most striking for the 17-kDa HS protein (HSP17) associated mostly with the thylakoid membranes. These findings together with the fact that the in vivo modulation of lipid saturation within cytoplasmic membrane had no effect on HS response suggest that thylakoid acts as a cellular thermometer where thermal stress is sensed and transduced into a cellular signal leading to the activation of HS genes.